Real time medical data acquisition over wireless ad-hoc network - A. Rashid, Rozeha (2005)
In the late millennium, biomedical revolution had stormed the world with amazing discoveries; including new ways to detect diseases, more effective ways of preventions, and more efficient ways of treating diseases. As such, there has been an increasing need to develop electronically based clinical information system (CIS) for medical diagnosis and treatment. Today, with the rapid development in the computer technology, international standards and broadband telecommunication networks, it is possible to have this clinical information on demand. This paper is an attempt where we utilize technology frontier to transmit real-time medical information to improve medical quality of service (QoS). A Linux based wireless mobile ad-hoc network test bed, MANET, is created. A smart electronic stethoscope (SES) system, which consists of a low cost electronic stethoscope, a multimedia personal computer, and a set of multimedia speakers, is designed and embedded inside the network. The system allows real-time digital recording of body acoustic, specifically the heartbeat, into a standard audio data file. It is also able to perform real-time plot of heartbeat pattern, store, do playback and amplify the recorded heart sound at unlimited track length. Socket programming is used to establish the connection between computers, enable real-time video streaming and remote control across the network. The successful transmission of real-time plot of heartbeat pattern over MANET shows its suitability for indoor use; i.e. in a hospital building, and enhances the mobility of CIS